Efektivitas Penggunaan Remdesivir terhadap Outcome Pasien COVID-19 di RSUD Embung Fatimah Kota Batam - Suhaera Suhaera; Messy Oktavia Hamzah; Henny Rachdiati (Universitas Muhammadiyah Surakarta, 2025)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by a new type of coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). This study was conducted to determine the effectiveness of the use of Remdesivir on the outcomes of COVID-19 patients at Embung Fatimah Hospital, Batam City. Remdesivir is the first drug to be approved by the US Food and Drug Administration (USFDA) as an Emergency Use Authorization (EUA) for hospital treatment administered to COVID-19 patients. This type of research is descriptive analytic with retrospective data collection. The analysis uses the Chi-square test to see the relationship between variables. The results obtained based on the gender of male patients by 53%, based on the age of 46-55 years by 32%, and based on the length of treatment the most days were found to be less than 14 days by 65%. The number of uses of Remdesivir in each COVID-19 patient is different, the highest result in the number of uses is less than equal to 6 injections by 81%, with the dose given is 200 mg on the first day, followed by 100 mg on day 2- 5. The results of the Chi-square test with a p-value of 0.029 show that the use of Remdesivir on the outcome of COVID-19 patients can be used.